2001
DOI: 10.1034/j.1600-0412.2001.080002130.x
|View full text |Cite
|
Sign up to set email alerts
|

A population based study of Swedish women’s opinions about antenatal, delivery and postpartum care

Abstract: This study has provided some useful information about women's opinion regarding antenatal, delivery and postpartum care which may be taken into account when instigating changes in the maternity care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
17
3
Order By: Relevance
“…Contrary to our findings, postpartum women have been reported to have a tendency to say they prefer the care they have received seeing it is difficult to express a preference for something else not knowing what services are, or could be made, available 17. The figures in this study are comparable with those of another Swedish study, of 2100 women, in which only 17% said they wanted to be able to go home within 24 hr 18. In the traditional maternity care, essentially healthy women run the risk of being medicalized.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, postpartum women have been reported to have a tendency to say they prefer the care they have received seeing it is difficult to express a preference for something else not knowing what services are, or could be made, available 17. The figures in this study are comparable with those of another Swedish study, of 2100 women, in which only 17% said they wanted to be able to go home within 24 hr 18. In the traditional maternity care, essentially healthy women run the risk of being medicalized.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings, that a large proportion (61.3%) of the women did not want to be discharged any earlier than 72 hours after childbirth, differ from the findings in a recent study of women in a large city in Sweden (30), in which 72% of the women wanted to be discharged by the 72 hours or sooner. Although early discharge in Sweden is well known and well established within the health care system (1), women in this specific geographic area are not prepared to be discharged within the limit of 72 hours set for early discharge.…”
Section: Discussioncontrasting
confidence: 57%
“…This is unsurprising as many studies have shown that women value health controls as the most important aspect of antenatal care, both during pregnancy and at other times in life (Drew et al. 1989, Ladfors et al. 2001, Hildingsson et al.…”
Section: Discussionmentioning
confidence: 99%